Antimicrobial activity and essential oils of Curcuma aeruginosa, Curcuma mangga, and Zingiber cassumunar from Malaysia - Tg Kamazeri, Tg Siti Amirah; Abd. Samah, Othman; Bakhtiar, M. Taher; Darnis, Deny Susanti; Qaralleh, Haitham (Elsevier, 2012)
OBJECTIVE: To analyze the chemical composition of the essential oils of Curcuma aeruginosa (C. aeruginosa), Curcuma mangga (C. mangga), and Zingiber cassumunar (Z. cassumunar), and study their antimicrobial activity.